2005
DOI: 10.1556/avet.53.2005.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Use of L-carnitine and humate in laying quail diets

Abstract: This experiment was carried out to determine the effects of using Lcarnitine and humate alone or in combination in quail diets on laying performance, egg traits and blood parameters. A total of 280 Japanese quails aged 10 weeks, divided into one control group and three treatment groups, were used. The diets of the first, second and third treatment groups were supplemented with 100 mg L-carnitine/kg, 1.5 g humate (Farmagülatör ® Dry Plus)/kg and 100 mg Lcarnitine + 1.5 g humate/kg, respectively. The experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
8
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 10 publications
8
8
2
1
Order By: Relevance
“…There were not significant differences in egg production in hens fed diets supplemented by L-carnitine ( Table 2). The results of the present study are also in agreement with the results of some researchers who found that L-carnitine supplementation had not significant effect on egg production of laying hens and laying quails (Celik et al 2004, Yalcin et al 2005and 2006. However, egg production values of laying hens fed 500 mg kg -1 L-carnitine were higher than those of control group (Bayram et al 1999).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…There were not significant differences in egg production in hens fed diets supplemented by L-carnitine ( Table 2). The results of the present study are also in agreement with the results of some researchers who found that L-carnitine supplementation had not significant effect on egg production of laying hens and laying quails (Celik et al 2004, Yalcin et al 2005and 2006. However, egg production values of laying hens fed 500 mg kg -1 L-carnitine were higher than those of control group (Bayram et al 1999).…”
Section: Resultssupporting
confidence: 93%
“…Adding L-carnitine to laying hen diets hadn't significant effect on feed intake (Table 2). Similar to the results of the present study, carnitine supplementation had not significant effect on the feed intake of laying hens and laying quails (Rabie et al 1997, Celik et al 2004, Yalcin et al 2005, 2006). There were not significant differences in egg production in hens fed diets supplemented by L-carnitine ( Table 2).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Ceylan et al (2003) and Bailey et al (1996) reported that supplementation level of 0.25% humate (Biomoss, a different product of humic acids) enhanced body weight gain (BWG) of broilers. But Kocabaglı et al (2002); Karaoglu et al (2004) and Yalcin et al (2005) have reported that 0.1-0.25% humate additions (HA) did not affect BWG of broilers. On the contrary, supplementation of 0.5-2.5% HA in ration decreased BWG of broilers (Rath et al, 2006).…”
Section: Humic Acidsmentioning
confidence: 99%
“…Yapılan araştırmada serum toplam protein, kolesterol, trigliserit, ALT, AST ve ALP düzeyleri bakımından gruplar arasında istatistik önem taşıyan farklılıkların görülmemesi bazı araştırıcıların bıldırcın (30,32) ve broyler (12,20,23) ile yapılan araştırma sonuçları ile uyum içerisindedir. Bununla birlikte Eder (15) L-karnitin uygulamasıyla plazmada kolesterol düzeyinin arttığını, bazı araştırıcılarda tavşanda (7) ve ratlarda (22) serum kolesterol ve trigliserit düzeylerinin azaldığını rapor etmişlerdir.…”
Section: Tartışma Ve Sonuçunclassified